SISTEM ENERGI DAN LATIHAN FISIK - Shadiqin, AR (Multilateral Jurnal Penjas Or, 2012)
Abstract :Sports symptomatic behavior change programmed by humans who do. Sports activities are often associated with indicators of successful development of a country, and to always be evaluated on a regular basis then held match the levels of the national championship, regional, Asian to Olympic. Activities of those games is an activity that continues to monitor progress regularly, good amenities / facilities, administration, and performance that can be recorded by the actors sport in each country. In maintaining homeostasis, the body´s system has a special line of muscle contraction energy supply, which is needed in regular activity and muscle contraction in activity. Therefore, performance should always be evaluated, then the increase in the development of the energy system becomes very important in the implementation of the exercise in order to create improved performance. Thus the development and improvement of energy systems in sport performance training needs special attention. Key words: energy systems, training. Abstract: Olahraga merupakan gejala perubahan perilaku gejala yang diprogram oleh manusia yang melakukan. Kegiatan olahraga sering dikaitkan dengan indikator keberhasilan pembangunan suatu negara, yang secara teratur selalu melakukan kejuaraan nasional, regional, Asia sampai pada tingkat Olimpiade. Kegiatan ini merupakan kegiatan yang terus memantau kemajuannya secara teratur, baik fasilitas/sarana, administrasi, dan kinerja yang dapat direkam oleh pelaku olahraga di setiap negara. Dalam mempertahankan homeostasis, sistem tubuh memiliki jalur khusus pasokan energi kontraksi otot, yang dibutuhkan dalam kegiatan rutin dan kontraksi otot dalam kegiatan. Oleh karena itu, kinerja harus selalu dievaluasi, maka peningkatan dalam pengembangan sistem energi menjadi sangat penting dalam pelaksanaan latihan dalam rangka menciptakan kinerja ditingkatkan. Dengan demikian pengembangan dan peningkatan sistem energi dalam pelatihan kinerja olahraga perlu perhatian khusus. Kata kunci: Sistem energi, Latihan Fisik.